Implementasi Aplikasi Cegah Ancaman untuk Pelaporan Tindak Kejahatan Berbasis Mobile Android - Abid Taufiqur Rohman; Elga Yuan Saputra; Dedi Gusriyanto; Alvian Andhi Gunawan (Jurusan Informatika STTR Cepu, 2024)
Crime is behavior that involves violations of laws or social norms prevailing in a society. In this context, criminal activities encompass a range of behaviors, from physical actions such as robbery or rape to non-physical actions such as fraud or money laundering. Crimes can harm individuals or groups, often triggering legal responses or law enforcement efforts to maintain order and justice in society. The Crime Threat Reporting Application is an Android-based mobile platform designed to provide a proactive solution in maintaining community safety and order. This research covers planning, system design, implementation, and black box testing phases. The application offers an intuitive user interface with key features such as Report Creation, Emergency Calls, and Report History. The research results indicate a significant improvement in the accessibility of geographical information, real-time monitoring, and reporting efficiency. Black box testing verifies the application's performance without detailing internal implementations. Thus, the Crime Threat Reporting Application can be considered an effective tool in supporting crime prevention and mitigation efforts, enabling active community participation in maintaining collective security.